Adaptasi Alat Ukur Learning Agility pada Karyawan untuk Meningkatkan Organizational Agility: Versi Bahasa Indonesia - Wardhani, Nurnaifah Selvia; Sulastiana, Marina; Ashriyana, Rezki (Universitas Islam Indonesia, 2022)
Learning agility is the willingness and the ability of individuals to engage in active learning in order to adapt activity opportunities from experience, and apply that learning lesson to successfully perform in the new and changing situations and conditions especially for reaching the organizational agility. Learning agility consists of four dimensions: people agility, results agility, mental agility, and change agility. The use of instruments in different cultural backgrounds requires an adaptation process to ensure the valid and reliable measurement results, but until now there has been no research on the adaptation of learning agility measurement instrument in Indonesia. The purpose of this study is to obtain and test the standardized Indonesian version of learning agility instrument. The adaptation process was carried out using the International Test Commission (2016) as a reference. Based on the results of the Confirmatory Factor Analysis (CFA) using JASP 0.13.1.0, it can be concluded that according to the theory, the learning agility model consists of four dimensions: people agility, results agility, mental agility, and change agility. It has a good fit model after several adjustment items are removed. It explains that the resulted model can describe the actual conditions, but with some conditions that must be taken into account.